Immune Cells in Thermogenic Adipose Depots: The Essential but Complex Relationship - Agueda-Oyarzabal, Marina; Emanuelli, Brice (Frontiers in Endocrinology, 2022)
Brown adipose tissue (BAT) is a unique organ in mammals capable of dissipating energy in form of heat. Additionally, white adipose tissue (WAT) can undergo browning and perform thermogenesis. In recent years, the research community has aimed to harness thermogenic depot functions for new therapeutic strategies against obesity and the metabolic syndrome; hence a comprehensive understanding of the thermogenic fat microenvironment is essential. Akin to WAT, immune cells also infiltrate and reside within the thermogenic adipose tissues and perform vital functions. As highly plastic organs, adipose depots rely on crucial interplay with these tissue resident cells to conserve their healthy state. Evidence has accumulated to show that different immune cell populations contribute to thermogenic adipose tissue homeostasis and activation through complex communicative networks. Furthermore, new studies have identified -but still not fully characterized further- numerous immune cell populations present in these depots. Here, we review the current knowledge of this emerging field by describing the immune cells that sway the thermogenic adipose depots, and the complex array of communications that influence tissue performance.